USE OF MENTAL MAPS IN BIOLOGY LESSONS (Academia Science Repository, 2023)
Different types of education are used today. One of these types of education is interactive education. A mental map is also used in the educational process. A mental map provides knowledge, understanding, application, synthesis and conclusion of the training. This article provides information about the use of mental maps in biology classes, and some examples of them are also given.